The Effect of Perceived Pension Fund Benefits on Work Motivation and Employee Performance Among Employees Approaching Retirement at PT XYZ Using the SEM-PLS Method - Yuniarso Dwiatmojo; Andi Joshua Saputra Valentino; Muhammad Nadiv Avilla; Jerry Heikal (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research aims to examine the relationship between pension fund benefits and employee performance and employee motivation to work as they approach retirement among PT XYZ employees. This study employs a quantitative approach utilizing a cross-sectional survey design. The data analysis method is the Structural Equation Model with Partial Least Squares (SEM-PLS), supported by SmartPLS software version 4. This study involved 410 employees aged 40 to 55 years, and 100 of them were selected purposively. The study utilizes one independent variable, perception pension fund benefits (X), which is measured by four indicators; then two dependent variables, namely employee performance (Y1) which is measured by five indicators and work motivation (Y2), which is measured by three indicators after elimination. Data were collected through a questionnaire that has a 5-point Likert scale. The results indicate that perceived pension fund benefits have a significant positive impact on employee performance (β = 0.273, p < 0.001). Conversely, perceived pension fund benefits have a significant negative impact on work motivation (β = -0.257, p < 0.001). The R-squared value for employee performance is 0.074, and the R-squared value for work motivation is 0.066, indicating that both variables are related. To improve employee punctuality, this study suggests the development of a more efficient time management program and monitoring system. In addition, job development programs can revitalize job design by offering challenging and meaningful work challenges for retired employees to maintain their work enthusiasm.